Upaya Pembentukan Nilai Karakter Peduli Sosial Melalui Pembelajaran IPS pada Siswa Kelas VIII di SMP Negeri 2 Sumbergempol Tulungagung - Ivana Tanti Larasari; Jani Jani (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This research is motivated by the decline in the value of social care character among adolescents as evidenced by the many cases of juvenile delinquency, namely lack of association, lack of caring, bullying, fighting and lack of sense of help in SMP Negeri 2 Sumbergempol Tulungagung. The existence of this background requires efforts and attention from social studies teachers in shaping social care attitudes in students. The research focus is: 1) How is the formation of social care character values through social studies learning of VIII grade students at SMP Negeri 2 Sumbergempol Tulungagung, 2) What are the supporting and inhibiting factors in the formation of social care character values through social studies learning of VIII grade students at SMP Negeri 2 Sumbergempol Tulungagung, 3) How is the impact of the formation of social care character values through social studies learning of VIII grade students at SMP Negeri 2 Sumbergempol Tulungagung. The objectives of this study are 1) To explain the formation of social care character values through social studies learning of grade VIII students at SMP Negeri 2 Sumbergempol Tulungagung, 2) To find out the supporting and inhibiting factors in the formation of social care character values through social studies learning of grade VIII students at SMP Negeri 2 Sumbergempol Tulungagung, 3) To determine the impact of the formation of social care character values through social studies learning of grade VIII students at SMP Negeri 2 Sumbergempol Tulungagung. This research uses a qualitative research approach with a descriptive type. Descriptive research is presented through words that are described, presented, analyzed and conclusions are drawn. The object of this research is the school and students of class VIII SMP Negeri 2 Sumbergempol Tulungagung. The data collection techniques used are interviews, observation and documentation.The results of this study indicate that the formation of social care character values through social studies learning is that teachers incorporate social care character values into lesson plans and develop syllabi and integrate social care character values through social studies learning. Supporting factors in shaping the character value of social care are exemplary teachers, school routine activities, and facilitating social activities and inhibiting factors are student awareness, family environment, cafes and parking lots and technological developments. The impact in forming the character value of social care has a positive impact, namely students will have an attitude of empathy, students have an attitude of helping and helping each other when in trouble, the creation of mutual cooperation activities at school, the creation of size and togetherness at school, the formation of a harmonious family, eliminating differences in social status between others.